Adsorption of Copper Ions on to Tyre Rubber - Sameer Al-Asheh; Fawzi Banat (Adsorption Science & Technology)
The adsorption capacity of untreated, chemically and physically activated tyre rubber towards Cu 2+ ions was studied. A comparison between these three types of adsorbent was performed in terms of dynamic and equilibrium considerations. The adsorption capacity of physically activated rubber was (marginally) greater than that of chemically activated rubber which, in turn, was greater than that of the untreated materials. The effects of activation temperature and time were considered in the physical activation process. Up to 97% of the Cu 2+ ions were adsorbed from aqueous solution when untreated, chemically or physically activated tyre rubber was employed as an adsorbent with initial metal concentrations of 20 mg/ml and 40 ppm, respectively. Increasing the adsorbent concentration resulted in a greater removal of metal ions from the aqueous solution, and increasing the Cu 2+ ion concentration in the presence of a constant adsorbent concentration increased the metal ion loading per unit weight of the adsorbent. An increase in the initial pH value of the metal solutions enhanced the adsorption process with all three adsorbents tested. It was demonstrated that the Freundlich and Langmuir isotherms were capable of describing the adsorption of Cu 2+ ions by the adsorbents under consideration reasonably well.